From heart to brain: a rare thrombotic presentation in homocystinuria - a case report - Mehta, Rachna; Rai, Rajesh; Inamdar, Prithi; Chavan, Bhushan; Rai, Nishmith (International Journal of Contemporary Pediatrics, 2025)
Homocystinuria is an uncommon autosomal recessive metabolic disorder caused by cystathionine β-synthase (CBS) deficiency, leading to impaired methionine metabolism and elevated homocysteine levels. The disorder presents with multisystem involvement, including neurocognitive deficits, lens dislocation (ectopia lentis), skeletal deformities such as osteoporosis, and a significant predisposition to thromboembolic phenomena, including deep vein thrombosis, sagittal sinus thrombosis, and myocardial infarction. Cerebral sinovenous thrombosis (CSVT), though rare, is a potentially life-threatening cerebrovascular event in children, often linked to risk factors such as dehydration, infection, trauma, malignancies, or underlying thrombophilias. While homocystinuria more commonly results in arterial strokes, CSVT as an initial clinical manifestation is exceedingly rare. Here, we present the case of an 8-year-old girl in whom CSVT was the first indicator of undiagnosed homocystinuria.